Helminth communities from two urban rat populations in Kuala Lumpur, Malaysia - Mohd Zain, Siti Nursheena; Behnke, Jerzy Marian; Lewis, John Watkin (BMC, 2012)
Background: The prevalence of parasitic infections among commensal animals such as black and brown rats in many tropical countries is high and in comparison with studies on rodents in temperate climates, little is known about the community structure of their parasites. Rodent borne parasites pose threats to human health since people living in close proximity to rodent populations can be exposed to infection. Methods: The helminth community structures of two urban rat populations in Kuala Lumpur, Malaysia were investigated. The rats were from two contrasting sites in the city caught over a period of 21 months in 2000-2002. Results: Eleven species of helminth parasites comprising seven nematodes (Heterakis spumosum, Mastophorus muris, Nippostrongylus brasiliensis, Syphacia muris, Pterygodermatites tani/whartoni, Gongylonema neoplasticum, Angiostrongylus malaysiensis), three cestodes (Hymenolepis (Rodentolepis) nana, H. diminuta and Taenia taeniaeformis) and one acanthocephalan (Moniliformis moniliformis) were recovered from 346 Rattus rattus and 104 R. norvegicus from two urban sites, Bangsar and Chow Kit, during 2000-2002. Rattus rattus harboured over 60% of all helminths compared with R. norvegicus, although both host species played a dominant role in the different sites with, for example R. norvegicus at Bangsar and R. rattus at Chow Kit accounting for most of the nematodes. Overall 80% of rats carried at least one species of helminth, with the highest prevalences being shown by H. diminuta (35%), H. spumosum (29.8%) and H. nana (28.4%). Nevertheless, there were marked differences in prevalence rates between sites and hosts. The influence of extrinsic (year, season and site) and intrinsic (species, sex and age) factors affecting infracommunity structure (abundance and prevalence of infection) and measures of component community structure were analyzed. Conclusions: Since at least two species of rat borne helminths in Kuala Lumpur have the potential to infect humans, and these showed high prevalences in the rats, the assessment and regular monitoring of infections carried by wild rodents have important roles to play in public health.